BAGAIMANA PENDIDIKAN KARAKTER DISELENGGARAKAN DI SEKOLAH - Harsono Harsono; Sri Hastuti (Jurnal Pendidikan Ilmu Sosial, 2017)
Our nation’s journey is getting dynamic. Problems are coming based on the era changing. The shape of our nation behavior is moving without any basic character concept. When the Demak emperor reached the peak of glory, continued by the colonialisms, Soekarno (Old Orde Era), Soeharto (New Orde Era), and Reformation era, the effort to build our nation never stop. Many people and treasure were sacrificed; however the results were not satisfying. Even the same problems repeated as historical theory.Through case analysis method, from small cases, the shape of unity is a fact. Character building that was stated in religion subject could not serve the satisfying results. Even nation character building is being more left behind compared to other nations. The new policy is needed to overcome those problems. Firstly, mother culture and national culture need to improve, whereas international culture is the second choice. Secondly, the implementation honesties, smart, queue culture trough exemplary are important. Wider proportion of psychomotor dimension will improve character building.